Global Positioning System and Strengthening of Geodetic Network of Nepal - Adhikary, Krishna Raj; Mahara, Shree Prakash (Journal on Geoinformatics, Nepal, 2004)
Nepal is a country of mountains The higher order geodetic points were mostly established on the top of mountains and these points were used for the geodetic network extension. Lower order geodetic control networks were established at different times and used for the surveying and mapping activities of the country. It has been found that the rate of convergence between north and south borders of Nepal to be 21±2 mm each year and the rate translation of Kathmandu to 55±3 mm/year to the plates. The most intense deformation in Nepal occurs along the belt of high mountains along its northern border resulting in a strain contraction rate normal to the Himalayan Arc. This belt is approximately 40 km wide and extends into southern Tibet.( 13). Recently Survey Department of Nepal has lunched a program of strengthening the existing geodetic network of Nepal and re-observed the position of higher order geodetic points by using geodetic GPS receivers to evaluate their position and thus to define the precision of the control points once again. This paper describes the observation procedure and the adjustment results of the existing higher order control network of Nepal established in different time using different types of equipment and techniques; and highlights the observation procedure and the result obtained after the post processing of the GPS observation results. Attempt has been made to give the procedure and identify the methodology for the re observation of existing higher order geodetic points by using GPS receiver and post processing the observed data so that the existing higher order geodetic points are within the given accuracy standard.